Avaliação das potencialidades e limitações da gestão dos resíduos sólidos sujeitos à logística reversa em municípios de pequeno porte na região central do estado de São Paulo - Chaves, Maria Angélica Milani Grizzo Barreto de (2016)
The publication of the SWNP - Solid Waste National Policy (Law 12.305/2010) was a landmark for the environmental issues in Brazil. One of the tools is product return strategy to the industry after consumption, through the Reverse Logistic (RL). However, RL requires proper structure and its implementation tends to be more difficult in small towns with small-scale generation and waste collection. Therefore, it is important to know and evaluate the local and regional reality, contemplating existing RL situations and allowing the identification of possible actions, which was the aim of this research that studied a set of eight small towns of the central region of São Paulo State. The information was initially obtained from contacts with representatives of local governments related to the environmental sector, later extending it to the various agents involved in waste subject to RL (trade associations, NGOs). The data were obtained from documentary research, as well as visits and local observations, and the results grouped into six categories (collection / receipt, storage, disposal, agreements and partnerships, educational activities and costs). At the end of survey, it has been found that the RL chain was consolidated in all municipalities in regard to pesticide containers and lubricating oils and in six of these municipalities, it is the same for the tires. On the other hand, the management of other wastes subject to LR showed weaknesses, where only three municipalities have proper disposal destination of electronic waste (EW) and batteries (due to existing partnerships) and only one for fluorescent lamps. The main limitations, we can mention: lack of knowledge and responsibilities in the shared responsibility chains; lack of political integration; informality in collection, storage, final disposal practices of some wastes specially batteries, EW, lamps. In terms of potential, it can be considered: little generation of some waste (batteries / EW) can be inducing factor for shared solutions for final disposal thereof; the geographical proximity among the cities studied facilitates logistics for possible partnerships.